2015
DOI: 10.1097/qai.0000000000000454
|View full text |Cite
|
Sign up to set email alerts
|

Mothers Who Sell Sex

Abstract: Motherhood is common among FSWs. The results indicate that FSWs who are mothers may have more exposure to health care because of seeking antenatal/perinatal services, presenting important opportunities for inclusion in the HIV continuum of care and to prevent vertical transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 55 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…Several studies have reported high HIV and STIs prevalence, physical and sexual violence, and limited access to healthcare services among FSWs; all of which have adverse effects on their pregnancy outcomes [14]. Not often recognized as mothers, health risks associated with pregnancy outcomes in FSWs remain overlooked [2, 5]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported high HIV and STIs prevalence, physical and sexual violence, and limited access to healthcare services among FSWs; all of which have adverse effects on their pregnancy outcomes [14]. Not often recognized as mothers, health risks associated with pregnancy outcomes in FSWs remain overlooked [2, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent research, however, suggests that despite complex reasons for pregnancy among FSWs, most desire to have or have children [3, 5, 6]. While some FSWs may consider having children as a way to solidify their relationship with a sex partner or leave sex work, others may be forced into sex work to provide for their children [1, 5, 7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,18 Many FSW become aware of their HIV infection as a result of opt out testing during pregnancy. 14,20,21 FSW commonly undergo voluntary HIV testing for frequent illness or deterioration of health. 14 To improve uptake of HIV care and treatment and prevent ongoing transmission, the barriers to HIV testing for FSW in sub-Saharan Africa must be delineated.…”
Section: Introductionmentioning
confidence: 99%
“…7 Characterization of the needs of these women is important, given their unique occupational risks, fertility-related concerns, child-care needs and potential barriers to accessing support services and health care emanating from social stigma and discrimination. 8,9 …”
Section: Introductionmentioning
confidence: 99%